Pengaruh Kompetensi, Sarana Dan Prasarana, Dan Lingkungan Kerja Terhadap Kinerja Tutor - Maulana Muaripin, Ary; Gunadi, Trida (Koaliansi : Cooperative Journal, 2023)
This study aims to determine: The effect of competence, facilities and infrastructure, and work environment on partially and simultaneously on the performance of tutors at the Technical Guidance Institute (Bimtek) Preparation for Selection of POLRI, TNI, and Kedinasan Taruna Adam Hawa Bandung. The population in this study were all tutors totaling 9 people. This research data was taken using a questionnaire method, then analyzed by descriptive analysis of percentage and multiple regression analysis. Based on the results of the Pearson Bivariate correlation analysis output (Pearson Product Moment) it can be concluded that the influence of competence, facilities and infrastructure, and work environment on the performance of tutors at the Technical Guidance Institute (Bimtek) for the Preparation of POLRI, TNI, and Service Taruna Adam Hawa Bandung has a partial and simultaneous influence.